Neuropsychiatry and behavioral neuroscience. - Cummings, Jeffrey L., ....-; Mega, Michael S., ....- (Oxford : University Press, 2003)
Contents: 1 Introduction 2 Neurobiological basis of behaviour 3 Neuropsychiatric assessment 4 Treatment of neuropsychiatric disorders 5 Principles of neuropsychiatry 6 Disorders of speech and language 7 Memory disorders 8 Visuospatial, visuoperceptual, and right hemisphere disturbances 9 Frontal lobe dysfunction 10 Dementia 11 Delirium 12 Psychosis, delusions, and schizophrenia 13 Hallucinations 14 Disturbances of mood and affect 15 Apathy and other personality disorders 16 Obsessive-compulsive disorder and syndromes with repetitive behaviours 17 Anxiety disorders 18 Movement disorders 19 Tics, startle syndromes, and myoclonus 20 Catatonia, motoric manifestations of psychiatric illnesses, and drug-induced motor system disturbances 21 Epilepsy and temporal-limbic syndromes 22 Dissociative states, multiple personality, and hysteria 23 Disturbances of sleep, appetite, and sexual function 24 Violence and aggression 25 Developmental neuropsychiatric syndromes 26 Focal brain disorders and related conditions
Keywords: Neurologie; Neuropsychiatrie